(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Aim. To determine the risk factors for the health of one-year-old children, depending on the conditions and lifestyle of the family. Materials and methods. To identify the risk factors that determine the health of children, the morbidity, conditions and lifestyle of 1,240 one-year-old children were studied. The work was carried out at the bases of family hospitals in four districts of the Tashkent city. Results The analysis of the "History of child development" showed that the risk of various pathologies was more often registered in children whose families were created on the basis of inter-family marriages, the presence of pathology of children at the time of birth, poor quality of care, and in children with a dysfunctional psychological climate of the family, etc. In children of this age, a relatively high incidence of respiratory diseases, congenital anomalies and individual conditions arising in the perinatal period has been established. Conclusions. To study the risk factors for the health of one year old kids, it is necessary to use a cohort method. The identified risk factors for children’s health should be the basis for the development of prognostic tables and individual preventive measures.